REPRESENTASI BUDAYA PATRIARKI DALAM FILM YUNI (2021) KARYA KAMILA ANDINI - dianfatiha rohmah (KRONIK : Journal of History Education and Historiography, 2022)
The film "Yuni" is a film released in 2021 directed by Kamila Andini, and written by Kamila Andini and Prisma Rudi. The film “Yuni” really highlights the existence of a patriarchal culture in a community group. Patriarchal culture is a culture that has a structure by placing the role of men as the main, central, and everything ruler. In a patriarchal culture, the role of women is limited so that women are shackled and discriminated against. This study aims to analyze the patriarchal culture in the film "Yuni". This research uses a qualitative approach with a descriptive type of research. The data used are sourced from the Yuni film and literature study. The data obtained were analyzed using the theory of liberal feminism, where the theory aims to explain the problems discussed using a women's perspective. The results of this study indicate that in the film Yuni highlights the existence of a patriarchal culture in the village. This patriarchal culture causes social problems, in the film, there are many stories about early marriage and domestic violence as well as discrimination in education for women. Keywords: Film, Patriarchal Culture, Discrimination